2018
DOI: 10.1101/411504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroanatomical correlates of food addiction and obesity in the general population

Abstract: The food addiction model suggests neurobiological similarities between substance-related and addictive disorders and obesity. While structural brain differences have been consistently reported in these conditions, little is known about the neuroanatomical correlates of food addiction. We therefore assessed whether food addiction, assessed with the Yale Food Addiction Scale (YFAS), related to obesity, personality and brain structure in a large population-based sample (n=625; 20-59 years old, 45% women). A highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Obesity has been associated with lower grey matter volume [11] and diminished cortical thickness [12]. The medial prefrontal cortex/orbitofrontal cortex, and temporal areas, such as the temporal pole, are some of the brain regions showing consistent reductions in volume and thickness associated with obesity in cross-sectional studies [8,[13][14][15][16][17] (Figure 1A). Moreover, studies on obesity using longitudinal designs have also reported alterations in grey matter.…”
Section: Brain Changes Associated With Obesitymentioning
confidence: 99%
“…Obesity has been associated with lower grey matter volume [11] and diminished cortical thickness [12]. The medial prefrontal cortex/orbitofrontal cortex, and temporal areas, such as the temporal pole, are some of the brain regions showing consistent reductions in volume and thickness associated with obesity in cross-sectional studies [8,[13][14][15][16][17] (Figure 1A). Moreover, studies on obesity using longitudinal designs have also reported alterations in grey matter.…”
Section: Brain Changes Associated With Obesitymentioning
confidence: 99%
“…To complete the discussion of the treatment of food produced by industry, we need to address the debated and controversial issue of food addiction. Food is a vital biological necessity and is one of the most complete and complex sensory stimulation systems with olfactory, visual, tactile, and gustatory stimuli that act simultaneously on different nerve centers and reward physiological needs [28].…”
Section: Food Addiction Eating Addiction and Eating Disordermentioning
confidence: 99%
“…[*] The agri-food industry is the leading manufacturing sector in the EU (with over EUR 1 trillion in turnover, 30 billion in trade surplus, 4.24 million in employment [28]. The interests at stake, inevitably, are carried forward by opposing sides on different sides.…”
Section: Food Addiction Eating Addiction and Eating Disordermentioning
confidence: 99%
“…We first estimated their effects in a model adjusting for baseline age and sex (model EA1) and then additionally controlling for logmFD (model EA2). As we previously reported correlated change in BMI and head motion in this sample (Beyer et al, 2019), we explored a refined model including average BMI and logmFD and change in both measures, along with baseline age and sex (model EA3). Here, we aimed to see whether any effect of change in BMI would be detectable when adjusting for the change in head motion.…”
Section: Exploratory Analysismentioning
confidence: 99%